Arrhythmias and sport activities in men without structural heart disease - Meinertz, T.; Zehender, M. (International Journal of Sports Medicine, 1996)
Siehe auch Artikel in Dtsch. Z. Sportmedizin, Köln 47/1996)S1, S, 167 - 176.